Exercise training at the maximal fat oxidation intensity improved health-related physical fitness in overweight middle-aged women - Jianxiong Wang; Sijie Tan; Liquan Cao (Elsevier, 2015)
Background/Objective: The purpose of this study was to test the hypothesis that exercise training at the maximal fat oxidation (FATmax) intensity would improve the health-related physical fitness in overweight middle-aged women. Methods: Thirty women (45-59 years old and BMI 28.2 ± 1.8 kg/m2) were randomly allocated into the Exercise and Control groups. Body composition, FATmax, predicted maximal oxygen uptake, heart function during submaximal exercise, stroke volume, left ventricular ejection fraction, trunk muscle strength, and body flexibility were measured before and after the experimental period. Results: Following the 10 weeks of supervised exercise training, the Exercise group achieved significant improvements in body composition, cardiovascular function, skeletal muscle strength, and body flexibility; whereas there were no changes in these variables of the Control group. There was also no significant change in daily energy intake for all participants before and after the interventions. Conclusion: The 10-week FATmax intensity training is an effective treatment to improve health-related physical fitness in overweight middle-aged women.